Professional Development of Lecturers at South African TVET Colleges through Coaching and Mentoring - Sihle Wendy Hlatjwako; Tendai Makwara; Lucky Sibanda; Elona N. Ndlovu (Social Sciences and Education Research Review, 2025)
This study examines the role of coaching and mentoring as professional development interventions aimed at enhancing lecturer competencies within South African Technical and Vocational Education and Training (TVET) colleges. Drawing on a systematic literature review, the paper synthesises recent empirical and theoretical contributions to identify how these interventions support the development of pedagogical, personal, social, and professional competencies. The findings indicate that while coaching and mentoring remain underutilised in the South African TVET sector, they present significant potential to address persistent skills gaps and align educator competencies with labour market needs. The study proposes a conceptual model grounded in General Systems Theory, outlining how coaching and mentoring, supported by institutional structures, contribute to sustained competency development. The model emphasises the importance of structured, context-specific approaches to lecturer support. The paper concludes by recommending the formal integration of coaching and mentoring frameworks into institutional policy to enhance the quality and relevance of TVET education.